Comparison of Bougainvillea spectabilis and Bougainvillea glabra species inhibited in Pakistan based on microscopic studies: Light microscope and scanning electron microscope. Issue 3 (29th November 2021) - Shaheen, Shabnum; Khan, Muhammad Asaf; Naeem, Muhammad Afzal; Shahid, Muhammad Naveed; Jaffer, Mehwish; Mukhtar, Hanan
Abstract: The anatomical variations of two plants from the Nyctaginaceae family, Bougainvillea spectabilis and Bougainvillea glabra, were studied using light and scanning electron microscopy methods in this work. Bougainvillea is a dicotyledonous with defensive traits that can withstand extreme (hot and dry) settings; according to the findings, crystal inclusions in cells, woody spines, and an abnormal development pattern are all features that help them survive against predators and are unique to this species. The Bougainvillea plant's leaves are arranged in simple pattern, alternate to each other along stem having an undulate leaves edge and an oval form. The xylem and phloem, palisade, parenchyma midrib, spongy mesophyll, raphide crystal bundles, and trichomes were all visible when bracts and leaves were transversally sectioned and dyed with toluidine blue O (TBO). The presence of crystals was confirmed by a detailed examination of the transverse leaves by using bright‐field and cross‐polarizing microscopy. Dissecting microscopic examination showed that all the leaves revealed leaves venation pattern that had midvein, lateral veins areoles, and trichomes. Although trichomes have been identified on both sides, a closer look at a cleaned leaf dyed with TBO showed multicellular abundant trichomes on adaxial surface. Stomata complexes were typically found on the abaxial surface of the leaf according to epidermal peels. Present studies also showed that on adaxial side, stomata were lesser in number or were absent and also showed that the morphologies of the pavement cells on the adaxial and abaxial sides of the leaf differed. Abstract : Morphology of Bougainvillea glabra (Hook) and Bougainvillea spectabilis Wild.